Re-newing the ancient: The Kāśīkhaṇḍa and Śaiva Vārāṇasī - Smith, Travis L. L. (Acta Orientalia Vilnensia, 2007)
University of Florida The present essay reassesses the central narratives of that renowned Purāṇic ‘glorification’ (māhātmya) of Vārāṇasī, the Kāśīkhaṇḍa. In retelling the ancient stories pertaining to Śaiva Vārāṇasī, the Kāśīkhaṇḍa embeds itself within the authoritative tradition of Vārāṇasī māhātmyas, even while effecting an ambitious literary project: a radical reconfiguration of the Śaiva landscape of the city. This reconfiguration would seek to legitimize new Śaiva forms—most prominently, an imperial temple dedicated to Viśveśvara—while reconciling them with Vārāṇasī’s existing Pāśupata infrastructure. Belying facile characterizations of Purāṇa as mere ‘myth’, the Kāśīkhaṇḍa composers took care in ensuring that the many, interwoven strands of its grand narrative of Vārāṇasī’s past were purposefully linked to ideological concerns of the present. A close reading of the Kāśīkhaṇḍa’s narrative strategies provokes a reevaluation of current scholarly understandings of Vārāṇasī history that view texts as imperfectly reflecting historical realities, rather than as actively constructing that very history.